(untitled) (Journal of Science Foundation, 2013)
Forty-four isolates of Phomopsis vexans were collected from eggplant producing areas of Bangladesh during the 2008-2009 growing seasons. The polymerase chain reaction (PCR) -variable number of tandem repeats (VNTR) technique was used to develop molecular markers. The MR-20 primer amplified template DNA for all isolates studied and resulted in distinct bands. The banding patterns of P. vexans isolates were separated into five groups after results with Taq polymerase. The highest genomic DNA concentration 50 ng/?l was found in the isolates of 8, 14, 26, 27 and 38, and the lowest concentration of genomic DNA was found 12.5 ng/?l in the isolates of 1, 2, 5, 15, 17, 22, 30, 31, 33, 34, 36, 40, 41, 42 and 43. Based on the fingerprinting the 44 isolates of Phomopsis vexans were categorized into five different groups. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14636 J. Sci. Foundation, 8(1&2): 131-140, June-December 2010